Design, modelling, prototyping and closed loop control of a mechanical ventilator for newborn babies - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2018)
Life support devices developed for use in the treatment of respiratory insufficiency are called mechanical ventilators. Mechanical ventilators that mimic gas exchange between the respiratory system organs and the atmosphere using different methods are critical medical care devices that allow the patient to maintain respiratory functions. In this study, a mechanical ventilator prototype was developed for use in transferring intensive care infants between medical institutions. The ventilator prototype is designed to be used as a CPAP (Continuous Positive Airway Pressure) device for neonatal resuscitation if desired. Prototyping work has been carried out taking into account the safety precautions and sensitivity parameters specified in the relevant standards of the neonatal ventilators. The ventilator can be able to operate with pressure and volume control. © 2018 IEEE.
Keywords: Cloosed Loop Control of Mechanical Ventilator; Infant Ventilator; Mechanical Ventilation; Medical Device Design; NICU Ventilation; Transport Ventilator